A 7-day high protein hypocaloric diet promotes cellular metabolic adaptations and attenuates lean mass loss in healthy males. (August 2017) - Furber, Matthew; Anton-Solanas, Ana; Koppe, Emma; Ashby, Charlotte; Roberts, Michael; Roberts, Justin
Summary: Mitochondrial quantity and density are associated with increased oxidative metabolism. It has been demonstrated that a hypocaloric high fat/low carbohydrate (HF/LC) diet can up-regulate transcriptional markers of mitochondrial biogenesis; this was yet to be explored in vivo subsequent to a high protein/low carbohydrate (HP/LC) diet. Thus the aims of the study were to explore such diets on transcriptional markers or mitochondrial biogenesis, body composition and resting metabolic rate (RMR). Forty-five healthy male participants were randomly assigned one of four intervention diets: eucaloric high protein low carbohydrate (PRO-EM), hypocaloric high protein low carbohydrate (PRO-ER), eucaloric high carbohydrate (CHO-EM) or hypocaloric high carbohydrate (CHO-ER). The macronutrient ratio of the high protein diet and high carbohydrate diets was 40:30:30% and 10:60:30% (PRO:CHO:FAT) respectively. Energy intake for the hypocaloric diets were calculated to match resting metabolic rate. Participants visited the laboratory on 3 occasions each separated by 7 days. On each visit body composition, resting metabolic rate and a muscle biopsy from the vastus lateralis was collected. Prior to visit 1 and 2 habitual diet was consumed which was used as a control, between visit 2 and 3 the intervention diet was consumed continuously for 7-days. No group × time effect was observed, however in the PRO-ER group a significant increase in AMPK, PGC-1α, SIRT1 and SIRT3 mRNA expression was observed post diet intervention groups ( p  < 0.05). No change was observed in any of the transcriptional markers in the other 3 groups. Despite ∼30% reduction in calorie intake no difference in lean mass (LM) loss was observed between the PRO-ER and CHO-EM groups. The results from this study suggest that a 7-day a high protein low carbohydrate hypocaloric diet increased AMPK, SIRT1 and PGC-1 α mRNA expression at rest, and also suggest that increased dietary protein may attenuate LM mass loss in a hypocaloric state.